2021
DOI: 10.1088/1361-6528/abd5e6
|View full text |Cite
|
Sign up to set email alerts
|

Ag-nanoparticles-loaded Ba0.85Ca0.15Ti0.9Zr0.1O3 for multicatalytic dye degradation

Abstract: Ba0.85Ca0.15Ti0.9Zr0.1O3 (BCZTO) ferroelectric ceramic loaded with Ag nanoparticles (NPs) was explored for its photo/piezocatalytic performance. The presence of Ag loading on BCZTO ceramic was confirmed using electron microscopes. X-ray photoelectron spectroscopy revealed the metallic chemical state of Ag NPs loaded on the surface of BCZTO ceramic. The absorbance spectrum of the Ag-loaded BCZTO sample showed a visible light absorption hump due to the phenomenon of surface plasmonic resonance. During the photoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…1,3 At present, literature is full of ultrasonic-induced dye degradation characterization using various piezoelectric materials such as BaTiO 3 , ZnO, Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O 3 , KNbO 3 , LiNbO 3 , Bi 2 WO 6 , etc. [4][5][6][7][8][9][10][11][12][13][14] These materials are widely explored in different nanostructures. It seems that piezocatalysis could be a potential technique for water cleaning and other catalytic applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3 At present, literature is full of ultrasonic-induced dye degradation characterization using various piezoelectric materials such as BaTiO 3 , ZnO, Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O 3 , KNbO 3 , LiNbO 3 , Bi 2 WO 6 , etc. [4][5][6][7][8][9][10][11][12][13][14] These materials are widely explored in different nanostructures. It seems that piezocatalysis could be a potential technique for water cleaning and other catalytic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Piezocatalysis still needs scientific exploration as there are multiple possibilities associated with enhancing the performance 1,3 . At present, literature is full of ultrasonic‐induced dye degradation characterization using various piezoelectric materials such as BaTiO 3 , ZnO, Ba 0.85 Ca 0.15 Zr 0.1 Ti 0.9 O 3 , KNbO 3 , LiNbO 3 , Bi 2 WO 6 , etc 4–14 . These materials are widely explored in different nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that LiNbO 3 has promising piezocatalytic dye degradation capability . Further, the loading of Ag noble metal nanoparticles (NPs) on ceramics can boost the electron–hole pair separation, which is desirable in catalysis reactions. , Thus, the incorporation of Ag NP-loaded LiNbO 3 into the PVDF film was expected to show superior piezocatalysis. Thus, in this article, the comparative piezocatalytic performance of PVDF, LiNbO 3 incorporated in PVDF, and Ag NP-loaded LiNbO 3 incorporated in PVDF films is reported.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is not much literature in this direction. In order to get visible light active catalytic reactions, one of the approaches is surface plasmon resonance (SPR) in which metal nanoparticles absorb visible light to enhance the photocatalytic and hydrogen evaluation activity of semiconductors 27,36‐44 . For SPR, various noble metals can be used.…”
Section: Introductionmentioning
confidence: 99%